Procalcitonin at 12–36 hours of fever for prediction of invasive bacterial infections in hospitalized febrile neonates - Romain, Anne-Sophie; Guedj, Romain; Chosidow, Anais; Mediamolle, Nicolas; Schnuriger, Aurélie; Vimont, Sophie; Ferrandiz, Charlène; Robin, Nicolas; Odièvre, Marie-Hélène; Grimprel, Emmanuel; Lorrot, Mathie (Frontiers in Pediatrics, 2022)
Aim: We aimed to investigate the performance of procalcitonin (PCT) assay between 12 and 36 hours after onset of fever (PCT H12-H36) to predict invasive bacterial infection (IBI) (ie, meningitis and/or bacteremia) in febrile neonates. Methods: We retrospectively included all febrile neonates hospitalized in the general pediatric department in a teaching hospital from January 2013 to December 2019. PCT assay  0.6 ng/ml was defined as negative. The primary outcome was to study the performance of PCT H12-H36 to predict IBI. Results: Out of 385 included neonates, IBI was ascertainable for 357 neonates (92.7%). We found 16 IBI: 3 meningitis and 13 bacteremia. Sensitivity and specificity of PCT H12-H36 in the identification of IBI were, respectively, 100% [95% CI 82.9% - 100%] and 71.8% [95% CI 66.8% - 76.6%], with positive and negative predictive values of 14.3% [95% CI 8.4% - 22.2%] and 100% [95% CI 98.8% - 100%] respectively. Of the 259 neonates who had a PCT assay within the first 12 hours of fever (< H12) and a PCT assay after H12-H36, 8 had IBI. Two of these 8 neonates had a negative < H12 PCT but a positive H12-H36 PCT. Conclusions: PCT H12-H36 did not miss any IBI whereas < H12 PCT could missed IBI diagnoses. PCT H12-H36 might be included in clinical decision rule to help physicians to stop early antibiotics in febrile neonates.